2017
DOI: 10.17269/cjph.108.6197
|View full text |Cite
|
Sign up to set email alerts
|

Slim cigarette smoking prevalence among Canadian youth smokers: Implications for federal standardized packaging legislation

Abstract: OBJECTIVES: Tobacco companies market to females and young people through slim cigarette design features and packaging. This study assessed the prevalence and perceptions of slim cigarette smoking in grades 9-12 student smokers across Canada using multiple data sources. (2015) were used. The prevalence and perceptions of slim cigarette smoking among current smokers were compared by sex and grade. METHODS:RESULTS: In all surveys, the rate of slim cigarette use was higher among females than males; however, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…All statistical analyses were conducted using SAS-callable SUDAAN (Version 11.0.3) to account for the complex sampling design and cross-sectional sampling weights. In addition to standard sociodemographic measures, covariates for regression models were selected because they were used in the construction of sampling weights 13 , 16 or because they were used in previous empirical research on slim cigarettes 18 , 19 or perceptions of the harmfulness of different tobacco products 20 . “Harm of own cigarette brand vs other brands” was included as a covariate in the model examining support for a slim ban because respondents were not directly asked whether they smoked a slim brand.…”
Section: Methodsmentioning
confidence: 99%
“…All statistical analyses were conducted using SAS-callable SUDAAN (Version 11.0.3) to account for the complex sampling design and cross-sectional sampling weights. In addition to standard sociodemographic measures, covariates for regression models were selected because they were used in the construction of sampling weights 13 , 16 or because they were used in previous empirical research on slim cigarettes 18 , 19 or perceptions of the harmfulness of different tobacco products 20 . “Harm of own cigarette brand vs other brands” was included as a covariate in the model examining support for a slim ban because respondents were not directly asked whether they smoked a slim brand.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies have found that the introduction and promotion of slim cigarettes in several English-speaking countries were associated with the increase of women there smoking [7][8][9][10][11]. More recent studies, including surveys, focus groups, and analysis of industry strategies, have found that the interest in slim cigarettes is not limited to English-speaking countries [8,[12][13][14][15][16]. For example, 2017 sales data showed substantial market shares of slim cigarettes in Russia (15.1%), Latvia (21.2%), Poland (27.9%), Belarus (30.5%), and South Korea (36.6%) [17].…”
Section: Introductionmentioning
confidence: 99%